Semiautomated aseptic preparation of patient-individual antineoplastic intravenous solutions: first experiences in a German hospital pharmacy - Schöning, Tilman; Artes, Adelia; Ehmann, Martin; Mertens, Mieke; Ober, Michael; Hoppe-Tichy, Torsten (European journal of hospital pharmacy, 2016)
In 2013, the PharmaHelp device was introduced to daily patient care at the University Hospital of Heidelberg in order to improve process and staff safety and health. It is a semiautomated device located in a safety workbench for aseptic preparation with weight-and-visual-supported process check as well as radio-frequency identification of bags and vials.
Published online first 3 September 2015
Gesehen am 20.05.2020